AMPEROMETRIC MICROBIOSENSOR FOR THE DETERMINATION OF CHOLINE (Journal of Sciences, Islamic Republic of Iran)
The construction and performance of an amperometric microbiosensor for the determination of choline chloride by immobilizing choline oxidase on a cellulose acetate membrane are described. The procedure of choline determination involved the electrochemical detection of enzymatically generated hydrogen peroxide. This microsensor has a linear response between 0.038-0.1 mM choline chloride. The response time is 1-2 minutes. The optimal working conditions for the microsensor were 0.1 M TRIS-HCl, pH = 8 at 30°C